PARADIGMA IDIOLOGI SISTEM EKONOMI DUNIA - Nur Hadi (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The paradigm of the capitalist and socialist economic system suggests that the production and consumption and distribution of wealth in principle have been established in accordance with applicable economic laws in the economic practice of society. Economic System is a system that regulates and establish economic relationships between people with a set of institutions in the order of life in the community or state. Almost every country has its own economic system. The paradigm of thought as the choice of economic system applied in a country depends on the mutual agreement of the country, in accordance with the constitution owned, the philosophy and ideology of the state in its economic system. The economic system is a system that regulates the economic conditions of a country in accordance with state conditions of the country itself. The capitalist economic system rests on private and private ownership of the means of production, distribution, and exchange. so that the three main things are full in private hands, the system is oriented to Jewish ideology. The socialist economic system is its economic activities ranging from planning, implementation, and supervision carried out by the government centrally, this system adopts the Christian ideology of religion. Communist economic system is an economic system in which the role of government as a regulator of all sources of economic activity, this system pivots on the ideology of Atheist. Pancasila economic system is a system of economic democracy, this system comes from the ideology of Pancasila. The Islamic economic system is an economic system based on the ideology of Tawheed (aqidah) Islam, Nubuwwah (prophet) Muhammad saw (the obligatory nature of Prophet and Messenger) and Khilafah (leadership) and Ma'ad (result)